Human Brain Phantom Modeling : Concentration and Temperature Effects on Relative Permittivity - Chew, Kim Mey; Rubita, Sudirman; Norhudah, Seman; Yong, Ching Yee (Trans Tech Publications Ltd., 2013)
This paper discusses on selecting the most appropriate material for developing human-like brain phantom. It aims to investigate the effect of concentration and temperature to relative permittivity of a sample. This phantom was developed as a human-like brain for tumour detection using microwave signal. Result shows that plant gelatine is a stable and appropriate material for building phantom than agar-agar. A few models were developed based on the proposed ratio of mixture.